Study on Domesticating Vigilantism in Ghana’s Fourth Republic: The Challenge Ahead - George Asekere (Modern Perspectives in Language, Literature and Education Vol. 5, 2021)
Political party vigilantism in Ghana has consistently been on the ascendency since the return to Constitutional rule in 1993. The effect of the violent activities of vigilante groups in Ghana cannot be delinked from elections. Their activities have usually been during and after elections across the country. By-elections in Atiwa, Akwatia, Chereponi, Talensi, Amenfi West and more recently Ayawaso West Wuogon, have all been marred by acts of violence. Ghana in 2017 recorded for the first time political party vigilante groups storming a courtroom in Kumasi and freeing some of their members standing trial after assaulting a regional security coordinator in the second largest region in the country – the Ashanti region. The paper seeks to highlight the dangers inherent in this rather negative development which could reverse the gains Ghana has made in consolidating its democracy. The author relied on secondary data including relevant media publications and statements from civil society organizations, political parties and religious bodies on vigilantism in Ghana. Findings show that the seed of vigilantism has been sowed and allowed to be nurtured to the extent that the parties have taken uncompromising positions in ending the canker because it borders on political power. A law has been passed but indications are that nothing much is changing. The National Peace Council has intervened yet there is no sign of a lasting solution to the problem. The paper concludes that all stakeholders especially the civil society organizations and the religious bodies ought to be objective and bold to openly name and shame political parties whose members engage in negative acts of vigilantism and urge the masses to vote against such parties or else the phenomenon will persist and its ramifications will be disastrous.